Land cover and land use changes in a Brazilian Cerrado landscape: drivers, processes, and patterns. Issue 5 (2nd September 2016) - Garcia, Andrea Santos; Ballester, Maria Victoria Ramos
ABSTRACT: The Cerrado is one of the most threatened biomes in South America. To create protection actions on any scale, understanding drivers and consequences of land cover and land use (LC and LU) is essential. This study defines the composition and configuration of a Cerrado landscape watershed from 1975 to 2011. Using Landsat images and socioeconomic census data, we determined the forces acting on LC and LU change processes and their consequences. LC classes differ from LU classes for landscape dominance and processes. Economic opportunities drove LU change and its spatial distribution was related to soil, streams, and roads. Deforestation was the main cause of forest loss but forest degradation was also important, with both presenting different patterns. The spatial distribution of bare soil was related to pasture in degradation and streams. Bare soil distribution was related to pasture in degradation and streams. We concluded that broad scale factors drove changes, but local features determined distribution, and that watershed conservation plans should act on different scales, with management being spatially explicit.